ANALISIS FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG GO PUBLIK DI BURSA EFEK JAKARTA - Yudhanta Sambharakreshna (Universitas Trunojoyo Madura, 2006)
Company Performance stability represent measuring rod tomaintain stock price. Company’s performance generally is mirrored infinancial statement company. Investor use financial statement ofcompany as a means of analysis for predicting company stock price.The means of analysis is ratio analysis considering fundamentalfactors influencing stock price. The fundamental factors influencingthe stock price are earning per share (EPS), dividend pay out ratio(DPR) , return on asset (ROA) and debt to equity ratio (DER). ThisResearch is implemented at bank industry which public go in stockexchange Jakarta. Process data use statistical aid software analysisthat is program SPSS v12 with test F to know dependent variableinfluence by simultaneous and test t to know dependent variableinfluence by partial. The analysis result show EPS, DPR, ROA andDER as simultaneous influence significant to stock price of bankindustry in stock exchange Jakarta. For partial test, EPS influencesignificant but DPR, ROA, and DER not influence significant to to stockprice of bank industry in stock exchange Jakarta.